What Has Driven the Decline of Infant Mortality in Kenya? - Demombynes, Gabriel; Trommlerová, Sofia Karina (World Bank, Washington, DC, 2012)
Substantial declines in infant and under-5 mortality have taken place in recent years in many countries in Sub-Saharan Africa. Kenya's infant mortality rate has fallen by 7.6 percent per year, the fastest rate of decline among the 20 countries in the region for which recent Demographic and Health Survey data is available. Kenya's rate of postneonatal deaths per 1,000 live births fell by more than half over a five-year period, dropping from 47 to 22, as measured using data from the 2003 and 2008-09 Demographic and Health Surveys. Among the possible causes of the decline are various targeted new public health initiatives and improved access to water and sanitation. A Oaxaca-Blinder decomposition using Demographic and Health Survey data shows that the increased ownership of insecticide-treated bednets in endemic malaria zones explains 39 percent of the decline in postneonatal mortality and 58 percent of the decline in infant mortality. Changes in other observable candidate factors do not explain substantial portions of the decline. The portion of the decline not explained may be associated with generalized trends such as the overall improvement in living standards that has taken place with economic growth. The widespread ownership of insecticide-treated bednets in areas of Kenya where malaria is rare suggests that better targeting of insecticide-treated bednet provision programs could improve the cost-effectiveness of such programs.